The effectiveness and safety of lienal polypeptide combined with chemotherapy or chemoradiotherapy for non-small cell lung cancer patients in real world. Issue 4 (29th January 2021) - Wang, Zhe; Liu, Junfeng
Abstract : Abstract: Chemotherapy/chemoradiotherapy are still the fundamental treatment for advanced lung cancers. To reduce side effects and improve life quality, lienal polypeptide (LP) could be used in combine with chemotherapy/chemoradiotherapy. Moreover, LP could regulate immune system and possibly reduce the side effects of chemotherapy drugs. In our study, 1658 lung cancer patients from 10 hospitals were retrospectively analyzed and divided into LP group and non-LP group by whether using LP during their treatment. Kaplan-Meier curves and Log-rank test was used to detect the difference of progression-free survival and overall-survival between the 2 groups. Two-sided P -values of less than .05 indicated statistical significance. All analyses were performed with SAS software (version 9.4 SAS Institute, Cary, NC). Results showed that the number of patients who had progressed diseases in LP group and control group were 532 (64.2%) and 507 (61.2%). Log Rank test showed that median progression-free survival for LP group was 12.1 months and 11.4 months for control group ( P  = .3478). Statistical analyses revealed significantly difference in overall-survival between LP group and control group (23.6 months vs 18.9 months, P  = .0177). The overall adverse effect rates were non-significantly different with 9.9% in the LP group and 9.3% in the non-LP group ( P  = .6767). In conclusion, our research results indicated that LP used in combination with chemotherapy/chemoradiotherapy was a safe and effective treatment for patients of advanced lung cancer. LP could also reduce the adverse effects of chemotherapy/chemoradiotherapy, thereby improving patients' life qualities, and potentially improving prognosis.